Expectations and resources in different contexts of development outcomes among Filipino youth - Sta. Maria, Madelene A.; Reyes, Melissa Lopez; Mansukhani, Roseann; Garo-Santiago, May Ann (Philippine journal of psychology, 2010)
"[This study] contains focus groups studies of Filipino youth's articulations and perspectives of their experiences in the family, peer group, school, and work place."